Biomechanics of Lumbar Spine Injury in Road Barrier Collision–Finite Element Study - Pachocki, L.; Daszkiewicz, K.; Łuczkiewicz, P.; Witkowski, W. (Frontiers in Bioengineering and Biotechnology, 2021)
Literature and field data from CIREN database have shown that lumbar spine injuries occur during car crashes. There are multiple hypotheses regarding how they occur; however, there is no biomechanical explanation for these injuries during collisions with road safety barriers (RSBs). Therefore, the objective of this study was to investigate the mechanics of vertebral fractures during car collisions with concrete RSBs. The finite element method was used for the numerical simulations. The global model of the car collision with the concrete RSB was created. The lumbar spine kinematics were extracted from the global simulation and then applied as boundary conditions to the detailed lumbar spine model. The results showed that during the collision, the occupant was elevated, and then dropped during the vehicle landing. This resulted in axial compression forces 2.6 kN with flexion bending moments 34.7 and 37.8 Nm in the L2 and L3 vertebrae. It was shown that the bending moment is the result of the longitudinal force on the eccentricity. The lumbar spine index for the L1–L5 section was 2.80, thus indicating a lumbar spine fracture. The minimum principal strain criterion of 7.4% and damage variable indicated L2 and L3 vertebrae and the inferior part of L1, as those potentially prone to fracture. This study found that lumbar spine fractures could occur as a consequence of vehicle landing during a collision with a concrete RSB mostly affecting the L1–L3 lumbar spine section. The fracture was caused by a combination of axial forces and flexion bending moments.